Performing arts and the royal Courts of Southeast Asia. volume 1: pusaka as documented heritage - Santaella, Mayco Axel * (BRILL, 2024)
This publication brings together current scholarship that focuses on the significance of performing arts heritage of royal courts in Southeast Asia. Royal courts have long been sites for the creation, exchange, maintenance, and development of myriad forms of performing arts and other distinctive cultural expressions. The first volume, Pusaka as Documented Heritage, consists of historical case studies, contexts and developments of royal court traditions, particularly in the nineteenth and twentieth centuries.